The Ocean's Vital Skin: Toward an Integrated Understanding of the Sea Surface Microlayer - Engel, Anja; Bange, Hermann W.; Cunliffe, Michael; Burrows, Susannah M.; Friedrichs, Gernot; Galgani, Luisa; Herrmann, Hartmut; Hertkorn, Norbert; Johnson, Martin; Liss, Peter S.; Quinn, Patricia K.; Schartau, Markus; et al. (Frontiers in Marine Science, 2017)
Despite the huge extent of the ocean’s surface, until now relatively little attention has been paid to the sea surface microlayer (SML) as the ultimate interface where heat, momentum and mass exchange between the ocean and the atmosphere takes place. Via the SML, large-scale environmental changes in the ocean such as warming, acidification, deoxygenation and eutrophication potentially influence cloud formation, precipitation and the global radiation balance. Due to the deep connectivity between biological, chemical and physical processes, studies of the SML may reveal multiple sensitivities to global and regional changes. Understanding the processes at the ocean’s surface, in particular involving the SML as an important and determinant interface, could therefore provide an essential contribution to the reduction of uncertainties regarding ocean-climate feedbacks. This review identifies gaps in our current knowledge of the SML and highlights a need to develop a holistic and mechanistic understanding of the diverse biological, chemical and physical processes occurring at the ocean-atmosphere interface. We advocate the development of strong interdisciplinary expertise and collaboration in order to bridge between ocean and atmospheric sciences. Although this will pose significant methodological challenges, such an initiative would represent a new role model for interdisciplinary research in Earth System sciences.